Interactive Notetaking for Content-Area Literacy, Levels 3-5 - Goodman, Judith (Classroom Resource Ser., 2018)
Help grades 3-5 students build content area literacy and increase retention through interactive notetaking! This resource provides creative strategies for notetaking to engage students in critical thinking and analysis across multiple subject areas.